2003
DOI: 10.1105/tpc.007831
|View full text |Cite
|
Sign up to set email alerts
|

EMF Genes Maintain Vegetative Development by Repressing the Flower Program in Arabidopsis

Abstract: The EMBRYONIC FLOWER ( EMF ) genes EMF1 and EMF2 are required to maintain vegetative development and repress flower development. EMF1 encodes a putative transcriptional regulator, and EMF2 encodes a Polycomb group protein homolog. We examined expression profiles of emf mutants using GeneChip technology. The high degree of overlap in expression changes from the wild type among the emf1 and emf2 mutants was consistent with the functional similarity between the two genes. Expression profiles of emf seedlings befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 55 publications
3
113
0
Order By: Relevance
“…S1A), whereas emf1-2 ult1-3 plants look liked the emf1-2 plants, producing oval-shaped, petioleless cotyledons that later become carpelloid, extremely short hypocotyls, and no leaf primordia (Supplemental Fig. S1A; Chen et al, 1997;Moon et al, 2003). Since the emf1-2 ult1-3 double mutants are similar to emf1-2 single mutants, we concluded that the ult1-3 mutation cannot rescue the emf1-2 phenotypes.…”
Section: Resultsmentioning
confidence: 94%
“…S1A), whereas emf1-2 ult1-3 plants look liked the emf1-2 plants, producing oval-shaped, petioleless cotyledons that later become carpelloid, extremely short hypocotyls, and no leaf primordia (Supplemental Fig. S1A; Chen et al, 1997;Moon et al, 2003). Since the emf1-2 ult1-3 double mutants are similar to emf1-2 single mutants, we concluded that the ult1-3 mutation cannot rescue the emf1-2 phenotypes.…”
Section: Resultsmentioning
confidence: 94%
“…According to previous results in Arabidopsis, the PRC1 RING finger proteins AtBMI1 and AtRING1 are required for the repression of the seed maturation program after germination, whereas EMF1 is required for the repression of the floral program during vegetative development (Moon et al, 2003;Calonje et al, 2008;Bratzel et al, 2010;Chen et al, 2010), indicating that different PRC1 components are crucial for the regulation of different subsets of targets. On the other hand, other results suggest that all these components are required for the regulation of a different subset of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming clear in Arabidopsis that modification of chromatin structure, by disruption of Polycomb group protein complexes at target loci, plays a major role in the floral transition. For example, the Polycomb group proteins EMBRYONIC FLOWER2 and FERTIL-IZATION-INDEPENDENT ENDOSPERM act as repressors of the floral homoeotic genes during embryo and vegetative development (Kinoshita et al, 2001;Yoshida et al, 2001;Moon et al, 2003). Specifically, the plant homeodomain finger protein, EARLY BOLTING IN SHORT DAYS, represses FT expression (Pineiro et al, 2003).…”
Section: First-time Flower Initiation In Poplarmentioning
confidence: 99%